Palace of Horticulture (Pacific Novelty Co.)
On verso: This beautiful structure is from the plans of Bakewell & Brown, San Francisco, and is constructed almost entirely of glass. Dimensions 672 by 320 feet. Dome 160 feet high and 152 feet in diameter. Cost, $341,000.